Study of Scheduling in Programming Languages of Multi-Core Processor - Hosseini-Rad, Mina; Abdulrozzagh-Nezzad, Majid; Javadi-Moghaddam, Seyyed-Mohammad (Data Science: Journal of Computing and Applied Informatics, 2019)
Over the recent decades, the nature of multi core processors caused changing the serial programming model to parallel mode. There are several programming languages for the parallel multi core processors and processors with different architectures that these languages have faced programmers to challenges to achieve higher performance. In additional, different scheduling methods in the programming languages for the multi core processors have significant impact on efficiency of the programming languages. Therefore, this article addresses the investigation of the conventional scheduling techniques in the programming languages of multi core processors which allows researcher to choose more suitable programing languages by comparing efficiency than application. Several languages such as Cilk++ØŒ OpenMPØŒ TBB and PThread were studied and their scheduling efficiency has been investigated by running Quick-Sort and Merge-Sort algorithms as well